The Numeracy Literacy Process of Fifth-Grade Elementary School Students in Solving Word Problems - Hidayat, Zulaikha; Syamsuddin, Agustan; Mukhlis , Mukhlis (Journal of Educational Sciences, 2025)
This study investigates the numeracy literacy skills of fifth-grade elementary students in comprehending and solving mathematical word problems. Conducted from February to April 2025, the research adopts a qualitative approach using a case study method. Four students participated two from SD Telkom Makassar and two from SD Islam Athirah Makassar. Data were gathered through classroom observations, in-depth interviews, and a literacy-based numeracy test. The test focused on four key competencies: generalizing, conjecturing, justifying, and convincing. To enhance the credibility of the results, data triangulation was applied across sources, methods, and time. The objective of this research is to understand how students engage in mathematical reasoning and identify the obstacles they face in progressing through the stages of problem-solving. The findings show that students who successfully solved problems were those who could interpret the context, recognize patterns, and explain their reasoning clearly. However, several participants were only able to conjecture or identify patterns but struggled to justify or convince others of their solutions. In conclusion, this study emphasizes the importance of developing instructional strategies that focus not only on producing correct answers but also on enhancing students’ reasoning processes. A key contribution of this research is its in-depth analysis of students’ thinking errors, particularly in structuring operations and maintaining accuracy in word problem responses.